Phylogenetic diversity of bacterial symbionts of Solemya hosts based on comparative sequence analysis of 16S rRNA genes. - Krueger, D M (1997)
The bacterial endosymbionts of two species of the bivalve genus Solemya from the Pacific Ocean, Solemya terraeregina and Solemya pusilla, were characterized. Prokaryotic cells resembling gram-negative bacteria were observed in the gills of both host species by transmission electron microscopy. The ultrastructure of the symbiosis in both host species is remarkably similar to that of all previously described Solemya spp. By using sequence data from 16S rRNA, the identity and evolutionary origins of the S. terraeregina and S. pusilla symbionts were also determined. Direct sequencing of PCR-amplified products from host gill DNA with primers specific for Bacteria 16S rRNA genes gave a single, unambiguous sequence for each of the two symbiont species. In situ hybridization with symbiont-specific oligonucleotide probes confirmed that these gene sequences belong to the bacteria residing in the hosts gills. Phylogenetic analyses of the 16S rRNA gene sequences by both distance and parsimony methods identify the S. terraeregina and S. pusilla symbionts as members of the gamma subdivision of the Proteobacteria. In contrast to symbionts of other bivalve families, which appear to be monophyletic, the S. terraeregina and S. pusilla symbionts share a more recent common ancestry with bacteria associating endosymbiotically with bivalves of the superfamily Lucinacea than with other Solemya symbionts (host species S. velum, S. occidentalis, and S. reidi). Overall, the 16S rRNA gene sequence data suggest that the symbionts of Solemya hosts represent at least two distinct bacterial lineages within the gamma-Proteobacteria. While it is increasingly clear that all extant species of Solemya live in symbiosis with specific bacteria, the associations appear to have multiple evolutionary origins.